PERANAN LAPIS GAMBUT TERHADAP MOBILITAS KARBON ORGANIK TERLARUT DAN PELEPASAN ION FE DAN AL PADA TANAH GAMBUT BERSUBSTRATUM BAHAN SULFIDIK (The Role of Peat Layer to DOC mobility and Fe and Al Ions release on Peatland with sulphidic substratum) - Z., Damanik,; B.H., Purwanto,; E, Hanudin, E; B, Radjagukguk, B (Universitas Palangka Raya, 2015)
ABSTRAKThe objectives of this study was to investigate the role of peat layer in the mobility of DOC and therelease of toxic elements from the underlying sulphidic materials for the various peat thicknesses. Thestudy was conducted in the soil department greenhouse, Faculty of Agriculture, Gadjah MadaUniversity from July to August 2015The experiment conducted in soil column made from PVC pipewhich have different peat layer thicknesses (without peat layer, < 50 cm, and 50-100 cm). Leachingwas conducted every week, with 500 cc distilled water for 4 weeks. Filtrate was collected, and pH,dissolved organic carbon, and Fe and Al ions was analyzed. The results of the study showed thatdiminution of thickness of the peat stratum of the soils underlaid by sulphidic material substratumcaused the release, and mobilization of Fe2+ and Al3+- ions along with leaching water which mighthave a significant impact in decreasing the quality of the surrounding water environments in the formof acidification, and enrichment of Fe2+ and Al3+ ions. In addition to the impact of the thickness of thepeat stratum, quality of the leaching water was also determined by the quality of the peat material,primarily the degree of decomposition, and concentration of DOC which played the role of chelatingagent for toxic ions such as Fe and Al.Key Word : Mobility, Organic Carbon, Ion Release, Sulphidic.